Systematical characterization and comparison of saponins in Achyranthes bidentata Blume and its three analogous species. Issue 5 (1st May 2022) - Wang, Yingying; Yao, Changliang; Wang, Mengyuan; Li, Jiayuan; Li, Zhenwei; Zhang, Jianqing; Wei, Wenlong; Bi, Qirui; Guo, De‐an
Abstract: Introduction: Achyranthes bidentata Blume (AB) has been used for a long time and is recorded in the Chinese Pharmacopoeia 2020 edition. It is commonly confused with Achyranthes aspera Linn (AA), Cyathula officinalis Kuan (CO) and Cyathula capitata (Wall.) Moq. (CC), belonging to the Achyranthes and Cyathula genera of the Amaranthaceae family. It is of great significance to recognize and distinguish chemical components of AB, AA, CO and CC. Objective: The purpose of this study was to develop an analytical method for in‐depth characterization and comparison of saponins in AB, AA, CO and CC. Methods: The extracts of AB, AA, CO and CC were analyzed by an RP × RP (C18 × Phenyl‐Hexyl) 2D LC system, eluted by acidic × ion pair mobile phases and detected by high resolution mass spectrometry. Fragmentation patterns of saponins were elucidated and proposed according to reference compounds or literature reports. Results: As a result, 839 saponins consisting of 81, 415, 99 and 392 components corresponding to AB, AA, CO and CC, respectively, were characterized, including 594 potentially new saponins. Meanwhile, 29 kinds of aglycones were elucidated, among which 25 were new ones. Besides, 14, 91, 37 and 174 characteristic potential quality markers with MS intensities exceeding 10, 000 were found in AB, AA, CO and CC, respectively. Conclusion: This comprehensive study not only expands our knowledge of the types of saponins in Achyranthes and Cyathula, but also reveals the differences among four kinds of analogous herbs (AB, AA, CO and CC), which facilitates the quality control of these herbal medicines in the future. Abstract : The purpose of this study was to develop an analytical method for in‐depth characterization and comparison of saponins from four species in Achyranthes and Cyathula genera. Eight hundred thirty‐nine saponins were characterized, including 594 potential new saponins. This comprehensive study not only enriched the types of saponins in Achyranthes and Cyathula genera but also revealed the differences among four kinds of analogous herbs, which facilitates the quality control of these herbal medicines in future.